HUBUNGAN LAYANAN PERPUSTAKAAN DENGAN MINAT BACA PESERTA DIDIK DI SMP NEGERI 2 PADANG PANJANG - Rahma, Hidayatur; Hasnawati, Hasnawati; Sriwahyuni, Eci (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
This research is motivated by the sub optimal library services provided to students, one of which is circulation services and reference services, resulting in low reading interest of students at SMP Negeri 2 Padang Panjang, especially in class VIII, and the lack of supporting facilities to increase students' reading interest. The problem limitation of this study is focused on the relationship between library services and students' reading interest at SMP Negeri 2 Padang Panjang. This study is a field research study using a quantitative approach. This research method uses correlational, namely to test whether there is a relationship between variable X and variable Y. The population in this study were all students of class VIII of SMPN 2 Padang Panjang. Sampling in this study was carried out using a purposive sampling technique. The classes selected as samples were VIII B and class VIII C, totaling 50 students. The data was processed using the statistical product and service solution (SPSS) program version 29. The results of the study showed that there was a significant relationship between library services and students' reading interest. To find out whether the relationship is significant or not, a product moment correlation test or r test was conducted. The results of the r test showed a correlation coefficient value of 0.361 which is greater than the r table of 0.284. The significance value of the correlation coefficient is 0.010, which is less than 0.05. Therefore, there is a low and significant relationship (correlation) between the library service variable (X) and the student reading interest variable (Y).